ANALISIS PENERAPAN AKUNTANSI PAJAK PERTAMBAHAN NILAI PADA PT. PELABUHAN INDONESIA I (PERSERO) - Fitriani Saragih (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
ABSTRACT The purpose of this study is to analyze the application of Value Added Tax Accounting at PT. Pelabuhan Indonesia I (Persero) and to find out what causes the difference in the amount of sales report commercial profit / loss, corporate income tax returns, and corporate income tax returns. The research method used descriptive approach. The type of data used in the form of primary data and secondary data. Data collection techniques with documentation and interviews. And data analysis technique used in research is descriptive analysis technique. The results showed that the application of Value Added Tax Accounting PT. Port of Indonesia is in accordance with the Law no. 42 Year 2009 and the factors that cause differences in the amount of sales in the report of commercial income / loss, corporate income tax returns, and tax returns VAT is the Income Tax Article 4 paragraph 2 and the difference in treatment. Keywords: Value Added Tax Accounting, Commercial Profit / Loss Report, SPT PPh Badan, and SPT Per VAT Period